Broadening horizons: research on ferroptosis in lung cancer and its potential therapeutic targets - Gao, Guangpeng; Zhang, Xindi (Frontiers in Immunology, 2025)
Ferroptosis is a novel form of cell death distinct from traditional mechanisms, characterized by the accumulation of iron ions and the production of lipid peroxides. It not only affects the survival of tumor cells but is also closely linked to changes in the tumor microenvironment. Lung cancer is one of the leading malignancies worldwide in terms of incidence and mortality, and its complex biological mechanisms and resistance make treatment challenging. Recent studies have shown that ferroptosis plays a key role in the onset and progression of lung cancer, with its intricate regulatory mechanisms influencing tumor development and response to therapy. As research into ferroptosis deepens, related molecular pathways, such as glutamate metabolism, iron metabolism, and antioxidant defense, have been gradually revealed. However, in clinical practice, ferroptosis-based therapeutic strategies for lung cancer are still in their early stages. Challenges remain, including the incomplete understanding of the specific mechanisms of ferroptosis, insufficient research on related regulatory factors, and limited insight into the interactions within the tumor microenvironment. Therefore, effective modulation of ferroptosis to enhance lung cancer treatment remains an urgent issue. This review summarizes the biological mechanisms of ferroptosis, analyzes the regulatory factors of ferroptosis in lung cancer cells and their interaction with the tumor microenvironment, and further explores potential therapeutic strategies targeting ferroptosis. By synthesizing the latest research, this paper aims to provide new perspectives and directions for lung cancer treatment, with the goal of advancing clinical applications.